2022
DOI: 10.2478/hukin-2022-0084
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Electromyographic Inter-Limb Asymmetry during a Standard versus a Sling Shot Assisted Bench Press Exercise

Abstract: The objective of this study was to compare peak surface electromyography (sEMG) activity of selected muscles along with inter-limb asymmetries between a control (CONT) and a Sling shot assisted (SS) bench press exercise. Ten resistance-trained males with at least three-year experience in resistance training (22.2 ± 1.9 years, 88.7 ± 11.2 kg, 179.5 ± 4.1 cm, bench press one-repetition maximum (1RM) = 127.3 ± 25.9 kg) performed the flat bench press exercise under two conditions at selected loads (85% and 100% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…On the contrary, previous studies that included the measurement of muscle activity by sEMG and the use of the SS showed a significant difference between the conditions, body sides, and applied external loads (6,36,38). The authors have shown that the use of the SS acutely reduces muscle activity, which, however, increases with increasing load, and that there are also significant differences in activity between the upper limbs (37). It also seems that the SS support increases the relative involvement of the nondominant limb while decreasing the sEMG muscle activity of both limbs (37).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the contrary, previous studies that included the measurement of muscle activity by sEMG and the use of the SS showed a significant difference between the conditions, body sides, and applied external loads (6,36,38). The authors have shown that the use of the SS acutely reduces muscle activity, which, however, increases with increasing load, and that there are also significant differences in activity between the upper limbs (37). It also seems that the SS support increases the relative involvement of the nondominant limb while decreasing the sEMG muscle activity of both limbs (37).…”
Section: Discussionmentioning
confidence: 99%
“…The authors have shown that the use of the SS acutely reduces muscle activity, which, however, increases with increasing load, and that there are also significant differences in activity between the upper limbs (37). It also seems that the SS support increases the relative involvement of the nondominant limb while decreasing the sEMG muscle activity of both limbs (37). Similarly, in this study, the dominant limb triceps brachii long head stiffness was significantly higher than that in the nondominant limb in the CONT condition, with no such differences in the SS condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations